Geografski prostor in turistična politika - Tkalčič, Marjan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
Apart from other tourist services tourism also markets geographic space in its broader sense, e.g. environment, natural beauties, cultural heritage, the life quality of local inhabitants, the organisation of the society, etc. The final product offered by a tourist destination consists of a variety of products, the identity of the destination and all the resources available. Tourism policy makes it possible for the private and public sector of the tourist destination to be brought into accord.
Keywords: družbena geografija; human geography; kulturna krajina; prostor; tourism; turistična geografija; turizem